Periarticular hypertonic dextrose vs intraarticular hyaluronic acid injections: a comparison of two minimally invasive techniques in the treatment of symptomatic knee osteoarthritis - Hosseini B (Dove Medical Press, 2019)
Behnam Hosseini,1 Mehrdad Taheri,1 Reza Pourroustaei Ardekani,1 Siamak Moradi,1 Morteza Kazempour Mofrad2 1Anesthesiology Research Center, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 2Department of Anesthesiology and Pain Medicine, AJA University of Medical Sciences, Tehran, IranCorrespondence: Mehrdad TaheriShahid Beheshti Anesthesiology Research Center, Shahid Beheshti University of Medical Sciences, Velenjak Street, Tehran 1985717413, IranTel +98 913 301 5829Fax +98 7 756 7840Email mehrdadtaheri@gmx.comBackground: Knee osteoarthritis (KOA) is the most prevailing form of joint disease. Despite the importance of minimally invasive therapeutic methods of KOA, there is a lack of evidence to compare intraarticular hyaluronic acid injection vs traditional dextrose prolotherapy.Objective: The aim was to compare the therapeutic effects of prolotherapy with hypertonic dextrose vs hyaluronic acid on function and pain in KOA cases.Materials and methods: One hundred and four KOA patients were enrolled and randomly assigned into two groups, each containing 52 patients. The hyaluronic acid (HA) group were treated by 2.5 mL of hyaluronic acid intraarticulary, and the hypertonic dextrose (HD) group received 10 mL of 12.5% dextrose periarticulary. Injections were repeated three times with 1-week intervals. Pain intensity, measured by visual analog scale, and knee function, scaled by the Western Ontario and McMaster university arthritis index scores were compared between the two groups before and 3 months after intervention. Pain and function of the knee improved significantly (P<0.001) in all patients. However, significantly more symptom relief was found in the HA over the HD group. Prolotherapy with hypertonic dextrose and intraarticular injection of hyaluronic acid results in the same pain reduction and symptom relief as a noninvasive therapeutic method of KOA.Conclusion: These results recommended intraarticular hyaluronic acid rather than prolotherapy by hypertonic dextrose for KOA symptoms relief.Keywords: prolotherapy, periarticular, intraarticular, dextrose, hyaluronic, knee osteoarthritis